Programa computacional para simulação da uniformidade de aplicação de água em irrigação por aspersão convencional e microaspersão - Menezes, Paulo Lopes de (2005)
This study was aimed for developing a computing program in graphic atmosphere to determine the uniformity and efficiency of water distribution in the irrigation system by sprinkler and trickle. The program was developed in the Basic Visual programming language where it was aimed to make a friendly interface for the user and generate graphics of uniformity in tests with distribution in mesh and radial collectors. To generate three-dimensional graphics it was used an external library to Visual Basic, destined to generate specialized graphics from past information as a parameter in time of the program execution. In the program a routine was implemented to make the linear interpolation of the collected blades in the radial test projecting the other measures, generating a square mould, to draw the distribution profile of the sprinkler or trickle in test and the uniformity and efficiency of water distribution to the several spacings with blade coverings. A series of data and real laboratory test for sprinkler and trickle irrigation, in radial and mesh distributions were submitted to the program aiming to test their sensitivity, where it was observed that the Christiansen´s Uniformity Coefficient (CUC) reduces as the space increases; that the test with radial distribution of collectors is statistically equivalent to the test with mesh distribution and that the program presents coherence in the information gotten through the comparison of their results with the presupposition values and generated by the program CATCH-3D.